- Prove by induction that for all natural numbers n >= 0: n sum i^2 = n(n + 1)(2n + 1)/6 i=1 n . Let S(n) be " sum i^2 = n(n + 1)(2n + 1)/6". i=1 . We prove that S(n) holds for all integers n >= 1. , Base: S(1) is trivially true, since: 1^2 = 1 = 1(1 + 1)(2 + 1)/6 . Ind. Hyp.: Let k >= 1 be an arbitrary integer and assume that S(k) holds. . Ind. Step: We prove S(k + 1) is true: k+1 k sum i^2 = (k + 1)^2 + sum i^2 i=1 i=1 = (k + 1)^2 + k(k + 1)(2k + 1)/6 By Ind. Hyp. = k^2 + 2k + 1 + (2k^3 + 3k^2 + k)/6 = (2k^3 + 9k^2 + 13k + 6)/6 = (k^2 + 3k + 2)(2k + 3)/6 = (k + 1)(k + 2)(2{k + 1} + 1)/6. - Prove by induction that for all natural numbers x >= 2 and n >= 0, x^n - 1 is divisible by x - 1. . Let S(n) to be "for all natural numbers x >= 2, x^n - 1 is divisible by x - 1". . We prove that S(n) is true for all natural numbers n. . Base: x^0 - 1 = 1 - 1 = 0 and 0 is definitly divisible by x - 1. . Ind. Hyp.: Assume that for an arbitrary natural number k >= 0, S(k) is true. . Ind. Step: We want to prove S(k + 1) holds. x^{k+1} - 1 = x * (x^k - 1) + (x - 1) By Ind. Hyps the first term on the right-hand-side is divisible by (x - 1), and the second term is (x - 1) which is trivially divisible by itself (since x >= 2 and therefore x - 1 =/= 0). Therefore Their sum (on the right-hand-side) is divisible by (x - 1), and so is x^{k+1} - 1. - Question 4.3:32 from text. Solution: it goes by induction. Consider an 2^n*2^n square. This can be divided into four 2^{n-1}*2^{n-1} squares (by cutting it vertically and horizontally from the middle). The point used in the induction step is, you will put an L-domino in the center such that it takes one square from each of the three 2^{n-1}*2^{n-2} that do not have that "removed" 1x1 square. This reduces the problem into four sub-problems of size 2^{n-1}*2^{n-1}.